Deficiencias en la (re)construcción constitucional del proceso de habeas data en el Perú - Loyola Ríos, Néstor (Pontificia Universidad Católica del Perú, 2025)
In this article, the author analyzes the shortcomings in the constitutional reconstruction of the habeas data process in Peru, focusing on the protection of the right of access to public information and informational self-determination. Through a review of the regulatory framework and its evolution, the article highlights the challenges in implementing the process established in the New Constitutional Procedural Code. Despite the reforms, the article points out technical and procedural flaws that make it difficult for both citizens and justice officials to understand. Furthermore, regulatory adjustments are proposed that could improve the effectiveness of this constitutional process, especially in relation to the mandatory nature of legal representation, the definitions of personal data banks, and the lack of alignment between administrative and jurisdictional regulations. The author concludes that it is urgent to modify the current legislation to facilitate access to justice and guarantee the protection of citizens’ fundamental rights.

En el presente artículo, el autor analiza las deficiencias en la reconstrucción constitucional del proceso de habeas data en Perú, con un enfoque en la protección del derecho de acceso a la información pública y la autodeterminación informativa. A través de una revisión del marco normativo y su evolución, se destacan los desafíos en la aplicación del proceso establecido en el Nuevo Código Procesal Constitucional. A pesar de las reformas, el artículo señala fallas técnicas y procesales que dificultan su comprensión tanto para los ciudadanos como para los operadores de justicia. Asimismo, se proponen ajustes normativos que puedan mejorar la efectividad de este proceso constitucional, especialmente en relación con la obligatoriedad del patrocinio legal, las definiciones de banco de datos personales y la falta de alineación entre las normas administrativas y jurisdiccionales. El autor concluye que es urgente modificar la legislación vigente para facilitar el acceso a la justicia y garantizar la protección de los derechos fundamentales de los ciudadanos.
Deficiencies in the constitutional (re)construction of the habeas data process in Peru
Keywords: Habeas data; Right of access to information; Informational self-determination; New Constitutional Procedural Code; Habeas data; Derecho de acceso a la información; Autodeterminación informativa; Nuevo Código Procesal Constitucional; https://purl.org/pe-repo/ocde/ford#5.05.01